The Diphthongs: The Obstacles for Indonesian Speakers of English - Desri Maria Sumbayak (Bina Nusantara University, 2009)
Article investigated the difficulties of Indonesian speaker of English in producing diphthongs /eɪ/ and /oʊ/. Five postgraduate students and five spouses of students at University of Canberra participated in this study. The participants were recorded in pronouncing /eɪ/ and /oʊ/ by reading lists of words and a story. The data were analysed by two Australian native speakers. Interrater reliability was calculated by using Cohen’s Kappa. The percentage was used to see the accurate diphthong realisations. The results showed that diphthong /oʊ/ was relatively more problematic than diphthong/eɪ/ and the students produced more diphthongs accurately than the spouses. The results also revealed that the ability to produce the diphthongs accurately was influenced by English proficiency and the type of tasks where diphthongs were pronounced.